Effect of Diets Supplemented With Yeast, Chitin, and Chitosan on the Growth, Immune, and Antioxidant Responses of the Freshwater Prawn Cryphiops (Cryphiops) caementarius - Walter Reyes-Avalos; Carlos Azañero-Díaz; Gladis Melgarejo-Velasquez; Carmen Yzásiga-Barrera; Brian Alegre-Calvo; Roberto Lezama-Salazar (Aquaculture Nutrition)
The purpose of the present research was to evaluate the effect of diets supplemented with activated yeast, crude chitin, and chitosan on the growth, immune, and antioxidant response of freshwater prawn Cryphiops (Cryphiops) caementarius. Adult male prawns were kept in individual culture vessels installed in aquarium tanks. The basal diet (control) was supplemented with activated Saccharomyces cerevisiae yeast (60 g/kg), crude chitin (20 g/kg), and chitosan (1 g/kg). Each dietary treatment consisted of three replicates. The diet supplemented with activated yeast causes greater growth, as well as a greater number of total hemocytes (82.54 × 105 cells/mL), semigranular (59 × 105 cells/mL), and granular (18.67 × 105 cells/mL) hemocytes and without atypical hemocytes. Furthermore, a higher number of hemocytes positive for prophenoloxidase (98%), a shorter hemolymph clotting time (42.87 s), a higher activity of acid phosphatase (12.50 U/mL) and glutathione-S-transferase (GST) (0.186 U/mL) were also observed in dietary yeast group. On the contrary, there were no differences in the activity of superoxide dismutase (SOD) enzyme in prawns from any dietary treatment. Results from this research demonstrate for the first time that the diet containing activated yeast increases the growth and immune response of the freshwater prawn through a significant increase in hemocyte and acid phosphatase levels, a decrease in hemolymph clotting time, and a greater number of proPO-positive hemocytes. However, activated yeast is not effective in increasing the activity of antioxidant enzymes SOD and GST. Therefore, the activated yeast diet can be useful to improve the aquaculture production of C. (C.) caementarius and possibly of other commercially important crustaceans.